Assessing the Present in Perspective of the Past: Experiences from a Chronicle Workshop on Company-Level Work Disability Management - Gensby, Ulrik (Nordic Journal of Working Life Studies, 2014)
Participatory approaches to jointly address development and change processes are increasingly applied in Nordic working life research. One approach, the Chronicle Workshop (CW), aims at facilitating collective history through collaborative exploration and joint analysis of organizational development and change processes to guide forthcoming change. This study presents the CW methodology as an interactive research process. The study examines how the CW can facilitate mutual understanding and explanation of sickness absence and return to work efforts in the healthcare workplace, and discuss the extent to which the CW methodology can inform researchers involved in organizational development and change to address some potential limitations that exist. The CW encouraged the expression of diverse perspectives, incorporating insight from different organizational levels, and identified various kinds of resources and dilemmas in mapping the collective history of company-level sickness absence and return to work efforts. More attention to consensus building and power relations, greater explicitness about theoretical groundings, researcher role, and follow-up action ought to be considered prospectively to develop the method further. Inspiration from action research principles and the combined use of critical realism and interactive research may guide future development of the CW methodology.